2022
DOI: 10.3390/ijms231810308
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocytes In Vitro Systems Allowing Study of OA

Abstract: Osteoarthritis (OA) is an extremely complex disease, as it combines both biological-chemical and mechanical aspects, and it also involves the entire joint consisting of various types of tissues, including cartilage and bone. This paper describes the methods of conducting cell cultures aimed at searching for the mechanical causes of OA development, therapeutic solutions, and methods of preventing the disease. It presents the systems for the cultivation of cartilage cells depending on the level of their structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…OA is an autoinflammatory disease mediated by chondrocytes involving multiple factors [ 17 ]. Chondrocytes are important factors in maintaining the homeostasis of articular cartilage [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…OA is an autoinflammatory disease mediated by chondrocytes involving multiple factors [ 17 ]. Chondrocytes are important factors in maintaining the homeostasis of articular cartilage [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the microstructure of cartilage is altered significantly, accompanied by water loss and degeneration of collagen fibers [29]. With increased OA severity, the synthesis and catabolism of cartilage are seriously unbalanced, coupled with the further increase and accumulation of MMPs, which aggravates the degradation of ECM [30]. Herein, similar to data presented by Xu [31], enhanced OS and inflammation were observed in AGEs-stimulated chondrocytes, which were markedly alleviated by Cabozantinib, implying that damage to chondrocytes by AGEs was signally relieved by Cabozantinib.…”
Section: Discussionmentioning
confidence: 99%
“…These models recapitulate several alterations in OA, including (i) increased inflammatory mediators (IL-1 β, TNF-α, COX-2, etc. ); (ii) the low synthesis of typical ECM molecules (Coll II, proteoglycans, sulphated GAG, HA and aggrecan) and inhibitors of matrix degradative enzymes such as tissue inhibitors of metalloproteinases (TIMPs); and (iii) an increased presence of catabolic mediators (collagen I and X and proteases such as MMPs and ADAMTSs) [109,110]. Notably, studies on articular chondrocytes of both human and animal species have shown the effect of n-3 PUFAs (DHA, EPA, ALA, RvD1 and PDX) in reversing the inflammation-induced up-regulation of catabolic mediators [65,[111][112][113][114][115][116] and in fostering the synthesis of anabolic markers [60,111].…”
Section: Effect Of N-3 Pufas In Oboa: Focus On Anti-inflammatory and ...mentioning
confidence: 99%